Prevalence and Clinico-diagnostic Profile of Hepatosplenomegaly in Children Admitted at a Tertiary Center in Kathmandu - Gautam, Uttara; Shakya, Kashyap Narsingh; Adhikari, Harihar; Thani, Kamal Prasad; Sharma, Sandip K. (Journal of Karnali Academy of Health Sciences, 2026)
Background: Hepatomegaly, hepatosplenomegaly or splenomegaly are clinical findings that can indicate a wide range of underlying conditions. Their causes are enteric fever, hepatitis, scrub typhus, acute liver failure, and leukemia. The aim of this study was to determine the prevalence of hepatomegaly, hepatosplenomegaly, and splenomegaly in admitted children along with various clinical features and diagnoses associated with them. Methods: A hospital-based descriptive cross-sectional study was done. The total enumeration sampling technique was used to enroll children aged one month to fourteen years admitted in pediatric ward. Informed consent was obtained from the parents and assent was taken in children more than seven years. Data were collected with proforma and entered in Microsoft excel 2016, transferred to SPSS 16 and Descriptive analysis was done. Results: Among 728 children admitted, 72 had either hepatomegaly, hepatosplenomegaly or splenomegaly with an overall prevalence of 9.89%. The majority (65.3%) had hepatomegaly, 30.55% had hepatosplenomegaly and 4.15% had splenomegaly. The prevalence of hepatomegaly, hepatosplenomegaly and splenomegaly were 6.46%, 3.02%, and 0.41% respectively. Infection was the most common cause of and fever was the most common presenting symptom in both hepatomegaly and hepatosplenomegaly. Conclusion: Hepatomegaly and hepatosplenomegaly are relatively common in children, often due to systemic infection. Splenomegaly usually occurs simultaneously with hepatomegaly; however, isolated splenomegaly can occur in a few cases. An awareness program about basic hygiene practices, vaccination, safe drinking water, and proper food handling can reduce the risk of infections like enteric fever.